Being you : a new science of consciousness - Seth, Anil (New York : Dutton Books, 2021)
Being you is an unprecedented tour of consciousness that's to new experimental evidence, much of white comes from Seth's own lab. His radical argument is that we do not perceive the world as it objectively is, but rather that we are prediction machines, constantly inventing our world and correcting our mistakes by the microsecond, and that we can now observe the biological mechanisms in the brain that accomplish this process of consciousness.
I: Level. The real problem -- Measuring consciousness -- Phi -- II: Content. Perceiving from the inside out -- The wizard of odds -- The beholder's share -- III: Self. Delirium -- Expect yourself -- Being a beast machine -- A fish in water -- Degrees of freedom -- IV: Other. Beyond human -- Machine minds.
Includes bibliographical references and index.
Keywords: SELF-PERCEPTION